THE RELATIONSHIP BETWEEN SELF-CONFIDENCE AND STUDENTS PERFORMANCE ‎IN BIOLOGY LAB EXCERCISE - Dina Rahma Fadlilah; Mieke Miarsyah; Eka Putri Azrai (EDUSAINS, 2017)
Biology lab exercise are an important aspect on learning process. However, the outcome of the lab activity might not come as the curriculum goals expected. It is due to several reasons. This paper try to measure the relationship between students’ character and students’ performance in Biology lab exercise. This study used self-confidence as a proxy of students’ character. A unique Indonesian high school datasets and simple regression analysis were used for this research. Evidence shows that pupils’ self-confidence 3% among other variables that determine students’ performance and it has positive but insignificant impacts on students performance. The evidence demonstrates there is a weak relationship between self-confidence and students performance in lab practice. Keyword: self confidence; performance of students; Biology practice